Alterações renais causadas pelo veneno de crotalus durissus cascavella e bloqueio farmacológico com indometacina, dexametasona e nefidipina - Martins, Alice Maria Costa (1997)
The ophidian accidents caused by Crotalus snakes have great importance for their toxicity and sequelae. Crotalus durissus cascavella is a common sub- specie in the northeast of Brazil. Wistar rats weighting between 240 and 280g were anaesthetized with sodium pentobarbital (50mg/kg). The right renal artery was cannulated through the upper mesenteric artery (Bowman, RH & Maack, T.E., Amer. J. Physiol. 226: 426-430, 1974) without blood flow interruption. The experiment started 20 min., after establishment renal function. The first 30 min. were considered internai control. Urine and perfusate samples were collected each lOmin. for further laboratorial analysis (sodium, potassium, inulin and osmolality). The venom was added to the system at 30 min. of perfusion. Dexamethasone, indomethacin and nifedipine were added 30 min. prior to the venom. The venom4 s effect was analysed under perfusion pressure (PP), urinary flow (UF), renal plasmatic flow (RPF), renal vascular resistence (RVR), glomerular filtration rate (GFR), tubular sodium transport (%TNa ), proximal tubular sodium transport (%pTNa+), tubular potassium transport (%TK+), proximal tubular potassium transport (%pTK+), and sodium (Na+t) and potassium (K+t) tissue concentration values. Venom infusion (10pg/ml) induced increase in PP (ctéo = 113,0 ± 0,48 mmHg vs Vôo = 131,0 ± 4,19 mmHg*) and UF (ct9o = 0,15 ± 0,006 ml.g.min’1 vs V90 = 0,30 ± 0,02 ml.g.min1*), with peak values at 60 and 90min, respectively. The RVR (ct]2o = 4,51 ± 0,19 mmHg/ml.g^.min’1 vs V120 = 7,26 ± 0,50 mmHg/ml.g^.min’1*) also increased, but RPF (cti2o = 15,20 ± 0,38 ml.g’1. min’1 vs V120 = 9,6 ± 0,42 ml. g^.min’1*), GFR (cti2o = 0,73 ± 0,04 ml.g’1. min’1 vs V120 = 0,54 ± 0,03 ml.g’1.min’1*)